Unified Solutions on Plastic Limit Internal Pressure for Metallic Elbows - Zhu, Q; Zhao, J.H.; Zhang, C.G.; Li, Y.; Wang, S. (Проблемы прочности, 2014)
With consideration of the intermediate principal
stress and different strength values in tension
and compression, the plastic analysis of
metallic elbows under internal pressure is conducted
based on the unified strength theory.
The unified solutions for elbows with constant
and variable wall thickness values, and those
with a local thinning are derived. Parametric
studies are carried out to investigate the dependence
between the unified strength theory parameter,
tension-compression ratio, bending
coefficient, and wall thickness. Comparing the
theoretical results and the experimental data, a
good agreement was observed. The results obtained
show that the unified solutions are versatile
in the theoretical analysis of metallic
elbows and can be reduced to many existing results.
The latent potentialities of metallic elbows
are fully achieved due to considering the intermediate
principal stress. The unified solutions have
an important practical value for the optimum
design and engineering application of metallic
elbows. На базе комплексной теории прочности проанализирована пластичность металлического
колена при внутреннем давлении с учетом промежуточного главного напряжения и различной
прочности при растяжении и сжатии. Получены комплексные решения для колен с одинаковой и разной толщиной стенок и локальным утонением. С целью изучения влияния параметра
комплексной теории прочности, степени растяжения–сжатия, коэффициента изгиба и
толщины стенок проведено параметрическое исследование. Сравнительный анализ расчетных и экспериментальных данных показал хорошее их соответствие. Установлено, что при
расчете металлических колен комплексные решения многофункциональны, о чем свидетельствуют полученные результаты. Учет промежуточного главного напряжения позволил выявить
скрытые потенциальные возможности металлических колен. Комплексные решения имеют
важное практическое значение для оптимального проектирования и технического применения металлических колен. На базі комплексної теорії міцності проаналізовано пластичність металічного коліна
при внутрішньому тиску з урахуванням проміжного головного напруження і різної
міцності при розтязі і стиску. Отримано комплексні розв’язки для колін, що мають
одинакову і різну товщину стінок і локальне стоншення. Із метою вивчення впливу
параметра комплексної теорії міцності, ступеня розтягу–стиску, коефіцієнта згину і
товщини стінок проведено параметричне дослідження. Порівняльний аналіз розрахункових і експериментальних даних показав хорошу їх відповідність. Установлено, що при розрахунку металічних колін комплексні розв’язки є багатофункціональними,
про що свідчать отримані дані. Урахування проміжного головного напруження
сприяло вивченню прихованих потенційних можливостей металічних колін. Комплексні розв’язки мають важливе практичне значення для оптимального проектування
і технічного використання металічних колін.